Increasing Understanding of the Independent Learning Curriculum SKKPD and its Implementation in Designing Service Implementation Plans (RPL) in Classical BK Courses For Guidance and Counseling Students of FKIP Universitas Bengkulu. - Saputra, Adif Jawadi; Mishbahuddin, Asyadani; Sinthia, Rita (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to improve students' understanding of the SKKPD of the Merdeka Belajar curriculum and its implementation in designing RPL in the Classical Counseling course of FKIP students at Bengkulu University by using experimental research for one semester. This research uses experiments (experimental research) with sampling using purposive sampling, namely Bengkulu University Guidance and Counseling students who are teaching Classical Counseling courses and processing research data using SPSS assistance with t-test analysis. that there is an increase in students' understanding scores of SKKPD and its implementation in RPL design. The increase in scores was obtained from before and after being given material for 1 semester in the Classical Counseling course with an average score before being given the material of 90.27 which was in the low category. After being given material, understanding of the SKKPD has increased with an average score of 133.77 which is included in the high category. so it can be concluded that there is an increase in students' understanding of the SKKPD and its implementation in designing